1997
DOI: 10.1143/jjap.36.4466
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Molecular Alignment of 3-n-Octadecylthiophene by Scanning Tunneling Microscope

Abstract: The molecular alignment of an alkylthiophene, 3-n-octadecylthiophene, on highly oriented pyrolytic graphite has been studied by scanning tunneling microscopy (STM). Lateral stripes with a period of 0.42 nm and vertical stripes with one of 5.0 nm are observed and assigned to molecular alignments of alkyl chains and thiophene rings connected by “head to head", respectively. An STM image of N-n-octadecylpyrrole is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…The maximum grafting density (s max ) of the polymer brushes as predicted by scaling laws is given by s max ¼ N À1/2 F 7/8 /a 2 where N is the degree of polymerization, F is the weight fraction in grafting solution, and a represents the segmental length of the monomer. 4,53 Thus, using F ¼ 1 (for the P3HT brushes formed from melt or a weight fraction of 100%) and a z 0.4 nm, 54,55 s max of P3HT brushes is 1.04 chains per nm 2 , suggesting that an experimental grafting density can be further increased. However, these calculations do not take into account (a) the bulkiness of the hexyl side groups as their steric hindrance could prevent the grafting density from reaching the theoretical value, and (b) the rigid rod like nature of the conjugated backbone.…”
Section: Grafting Densitymentioning
confidence: 99%
“…The maximum grafting density (s max ) of the polymer brushes as predicted by scaling laws is given by s max ¼ N À1/2 F 7/8 /a 2 where N is the degree of polymerization, F is the weight fraction in grafting solution, and a represents the segmental length of the monomer. 4,53 Thus, using F ¼ 1 (for the P3HT brushes formed from melt or a weight fraction of 100%) and a z 0.4 nm, 54,55 s max of P3HT brushes is 1.04 chains per nm 2 , suggesting that an experimental grafting density can be further increased. However, these calculations do not take into account (a) the bulkiness of the hexyl side groups as their steric hindrance could prevent the grafting density from reaching the theoretical value, and (b) the rigid rod like nature of the conjugated backbone.…”
Section: Grafting Densitymentioning
confidence: 99%
“…Nevertheless, in order to generate materials with the desired properties, they should be incorporated in supramolecular structures, such as, for example, ordered monolayers. Scanning tunneling microscopy (STM) in solution revealed that the crystallographic order of nonpolar alkylthiophene derivatives is determined by the length of their alkyl chains. Even polythiophenes modified by attachment of alkyl chains built up ordered structures at the liquid/solid interface , STM measurements of thiophenes under ultrahigh vacuum (UHV) conditions were also performed on nonpolar thiophene derivatives on Ag. …”
Section: Introductionmentioning
confidence: 99%
“…Though the amide-dipoles would cancel for these species if they adopted head-to-head packing (SI Figure S9), calculations suggest that the dipole stabilization would be less for the 2-amide than for the 3-amide (SI Tables S1 and S2) and that the packing may be less dense (SI Figure S9) or involve conformational strain that increases the total energy (SI Table S2). Head-to-head packing is observed for 3-octadecylthiophene (SI Figure S5) 10 and 4-substituted pyridine species. 19 Despite the change in attachment chemistry from alkyl to amide, the sulfur atom forms the electron-rich end of the local ring dipole.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3,4 While monolayers of many structurally elaborate thiophenecontaining molecules have been imaged at the liquid/HOPG interface, 5−9 few simple thiophenes have been examined. 10,11 While the influence of π−π, van der Waals, and hydrogenbonding interactions on self-assembly has been studied in detail, dipole−dipole interactions have been less intensively investigated and are more controversial. At the graphite interface, dipole−dipole interactions influence the self-assembly of polar fluorenone complexes, 12 anthracenes with ether side chains, 13 hexabenzocoronene derivatives, 14 and halogen-substituted oligothiophenes.…”
Section: ■ Introductionmentioning
confidence: 99%